First High‐Speed Video Camera Observations of a Lightning Flash Associated With a Downward Terrestrial Gamma‐Ray Flash - R. U. Abbasi; M. M. F. Saba; J. W. Belz; P. R. Krehbiel; W. Rison; N. Kieu; D. R. daSilva; M. A. Stanley; Dan Rodeheffer; J. Remington; J. Mazich; R. LeVon; et al. (Geophysical Research Letters)
Abstract In this paper, we present the first high‐speed video observation of a cloud‐to‐ground lightning flash and its associated downward‐directed Terrestrial Gamma‐ray Flash (TGF). The optical emission of the event was observed by a high‐speed video camera running at 40,000 frames per second in conjunction with the Telescope Array Surface Detector, Lightning Mapping Array, interferometer, electric‐field fast antenna, and the National Lightning Detection Network. The cloud‐to‐ground flash associated with the observed TGF was formed by a fast downward leader followed by a very intense return stroke peak current of −154 kA. The TGF occurred while the downward leader was below cloud base, and even when it was halfway in its propagation to ground. The suite of gamma‐ray and lightning instruments, timing resolution, and source proximity offer us detailed information and therefore a unique look at the TGF phenomena.